Culture and Performance Appraisal Processes and Practices: Critical Insights from the South African Public Sector - Masiya, Tyanai; Kanengoni, Herbert (Facets of Managing in Cross-Cultural Diversity, 2021)
This chapter provides an insight into culture and performance appraisal practices and processes in the South African public sector. Performance appraisal is an element of performance management – a relatively new phenomenon in many African countries, which depends on western-oriented reform initiatives and is becoming increasingly more popular. Literary discussions about cultural influences on performance appraisals in South Africa and some African countries are limited. Performance appraisal is a complex process whose outcomes are used for decision-making in an organisation – to improve employee performance. This chapter concludes that many African practices, attitudes and customs affect the effective use of performance appraisals in improving employee performance in the public sector. The chapter contributes to findings regarding cultural influences on performance appraisal in the South African public sector and the African public sector in general.